Michel Foucault on the Deployment of Sexuality - Nietlong, Joseph (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
One of Foucault’s central tenets is that sexuality is a construct, a fabrication-invented to be wielded as a tool in the dissemination of what he calls bio-power. Therefore movements of sexual identity or sexual liberation are integral parts of that conspiracy mechanism for power domination (repression is not the most general form of domination). Hence belief that one is resisting repression, whether by self-knowledge or by telling the truth supports domination because it masks the real working of power. In this paper, I wish to first make an exposition of how Foucault arrived at this notion, after which I shall attempt to examine the strength and validity of this claim.